Towards sustainable kinetic resolution, a combination of bio-catalysis, flow chemistry and bio-based solvents. Issue 1 (11th December 2017) - Iemhoff, Andree; Sherwood, James; McElroy, Con R.; Hunt, Andrew J.
Abstract : The esterification of 2-phenylpropionic acid was investigated as a model system for enzyme catalysed (CALB, Novozyme 435) reactions in bio-based solvents. Abstract : The esterification of 2-phenylpropionic acid was investigated as a model system for enzyme catalysed (CALB, Novozyme 435) reactions in bio-based solvents. A multi-parameter correlation taking into account solvent parameters was developed to explain experimental observations. A continuous flow process using p -cymene as the solvent was operated over several weeks, thus combining a sustainable solvent and flow chemistry for kinetic resolution.